Dampak Terjadinya Stunting terhadap Perkembangan Kognitif Anak : Literature Review - Rakhmalia Imeldawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Stunting, a growth disorder in young children caused by chronic malnutrition, can significantly impair a child's growth and development, especially cognitive development. This paper reviews the scientific evidence linking to cognitive delay. The author uses data from reference journal articles and several theories published between 2019 and 2024 accessed through Google Scholar, PubMed, Scopus, NCBI, and others using keywords such as